"You are mum and then they are mum": Negotiating roles, relationships, and contact in out‐of‐home care. Issue 3 (20th January 2022) - Collings, Susan; Wright, Amy C.
Abstract: Objective: Birth family contact can be undermined by relationship difficulties between adults from children's two families, especially in relation to role ambiguity for mother figures. Research to understand relationships between birth mothers and female caregivers across all placement types is needed. Background: In Australia, children in long‐term care, guardianship, and open adoption have direct contact with members of their birth families. The extent to which maternal figures work together is critical to children's ability to enjoy ongoing birth family connections, particularly First Nations children, who are overrepresented in out‐of‐home care. Method: Qualitative methods were used to understand the personal attributes that influence relationships between five dyads of birth mothers and their child's female caregivers in New South Wales. Four were foster or kinship carers, two had adoptions underway, and one was a legal guardian. Three birth mothers identified as Aboriginal, and no caregivers did so. Analysis mapped birth mothers' acceptance and carers' communicative openness and interpreted influences of interpersonal skills, contact, and power dynamics on relationship quality. Results: Positive and natural interactions between children' mother figures can exist irrespective of legal arrangement when both are able to demonstrate emotional competence and learn relationship‐building skills and overcome power imbalances. Conclusion: The complexity of managing relationships in the context of permanent child removal is influenced by how well children's two mother figures renegotiate their roles. Implications: Families need support to discuss the goals and purpose of contact and identify relational resources and challenges. Professionals could use visit coaching to support children's two families in navigating contact.